Evolution of media repositories and archives the clipper project - Casey, John (My University, 2017)
Poster presented by John Casey, City of Glasgow College - Evolution of Media Repositories and Archives: The Clipper Project The beginnings of a data citation toolkit for audio-visual data
Keywords: media repositories